'Engaging People and Ideas': Memories, Meaning Making and the European Educational Research Association. (August 2014) - Pataki, Gyöngyvér
This article seeks to reveal patterns of the discursive and interpretative culture of the European Educational Research Association (EERA) in an attempt to contribute directly to the discussion about the social and cultural integrity of the association. It looks beyond the network and community approaches of transnational research associations and suggests instead that the communicative aspects of the organisation should be considered. Within this framework the article aims to address the questions to what extent can EERA be considered as an intellectual home, and what motivates researchers to be engaged with EERA activities? In 2013 four group interviews and 26 semi-structured interviews were carried out in an effort to delineate what lends stability and intimacy to a broad European umbrella organisation. Respondents were asked to share their experiences with EERA and their reflection on their contribution to it. The data reveal that there is a delicate balance between activity and representation within the association and that there is a constant reflection on, as well as a desire towards, inclusiveness in terms of both ideas and colleagues. The data show that researchers enter EERA seeking their research identity and slowly realise that the only way to establish their belonging to the association is their constant contribution. It is possible to discern that a dynamic element — constant contribution in communication — gives EERA its integrity and intimacy.